ANALISIS UMUR FATIK RANGKA PENYANGGA AILERON FLIGHT CONTROL SIMULATOR BERKAPASITAS 101KG DI PT MMF - Ready Kresna Nanda Suprapto (Politeknik Penerbangan Surabaya, 2021)
This study examines the fatigue life of the aileron flight control simulator support frame using the finite element method. Design and calculation of frame fatigue life using Solidworks 2020 software. In this study, 3 design variables were used, namely: Initial, New, and Alternative. While the material used in this study using ASTM A500. The simulation results of the initial, new and alternative design aileron support frames using ASTM A36 material have a minimum fatigue life of 1.41 x 105, 6.50 x 106, and 1.00 x 107 Â cycles, respectively. While the Initial, New and Alternative designs with ASTM A500 material have a minimum fatigue life of 1.04 x 104, 3.71 x 104, and 1.00 x 107 cycles